Imbalance between inflammatory and regulatory cord blood B cells following pre-term birth. (June 2021) - Busse, Mandy; Redlich, Anke; Hartig, Roland; Costa, Serban-Dan; Rathert, Henning; Fest, Stefan; Zenclussen, Ana Claudia
Highlights: Proinflammatory cytokines are enhanced in amniotic fluid and cord blood (CB) of pre-term birth (PTB) compared to term. CB from PTB contains a decreased percentage of CD24 hi CD38 hi CD19+ and CD1d hi CD5+ Breg cells in comparison to term. The ability of B cells to convert into Breg cells in vitro is diminished in PTB. B cells from CB secrete higher levels of proinflammatory cytokines in PTB vs term. Abstract: Preterm birth (PTB) is one of the most frequent pregnancy complications. It affects millions of babies each year worldwide and is associated with increased morbidity and mortality. PTB-associated alterations in the maternal immune response may have a direct effect on the developing fetal immune system. Having recently shown that B regulatory (Breg) cells are decreased in number and functionally impaired in maternal blood from women delivering preterm, we now addressed the question whether the adaptive immune system is also altered in cord blood (CB) after the onset of PTB. PTB was associated with increased concentrations of IL-6, TNF-α and IL-21 in CB and enhanced IL-6, but decreased IFN-γ and IL-4 in amniotic fluid (AF) samples compared to term delivery (TD). We found no differences in the frequency of CD19 + B cells, CD4 + T cells or CD4+Foxp3+CD25+ T regulatory (Treg) cells in CB cells in PTB vs TD. The frequency of CD86 + B cells was increased, while the percentage of CD24 hi CD38 hi CD19 + Breg and CD1d hi CD5+ Breg cells and the ability of B cells to convert into Breg cells was diminished in PTB compared to TD. CB B cells from PTB secreted more IL-6, TNF-α, IL-9 and IL-2 compared to B cells obtained from term samples. We conclude that, after PTB onset, a shift from immunoregulation towards inflammation takes place in CB cells that are reportedly representative of the fetal compartment. B cells have a substantial contribution herein. This phenomenon might account for the observed enhanced mortality and morbidity in prematurely born infants. Further studies will clarify how to employ this easy-to-obtain information for closely monitoring newborns at risk.